ADULT LEARNING: TRENDS AND OPPORTUNITIES IN THE ORGANIZATION - Čižikienė, Janina; Urmanavičienė, Audronė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The European Union's education and lifelong learning policy stresses informal learning within the society. The article aims to review the concept of lifelong learning and to analyze opportunities for continuous learning process in organizations. New technologies, innovations in the workplace and professional training encourage employees to improve constantly and awareness of the importance of lifelong learning can help to secure their future in a changing labor market. Research methods applied were as following: literature and document analysis, expert interviews, analysis of the results and interpretation. The article presents a review of scientific literature and research data reveals leaders’ approach to employees' willingness to raise their qualification constantly and the organization's opportunities. The survey showed that employers want to have a highly qualified staff meeting the requirements of the organization, but do not always have sufficient funds for professional development.